Religion in America - Pearce, Lisa D. (Lisa Deanne), 1971-; Gilliland, Claire C. (Sociology in the 21st century (University of California Press), 2020)
"Written in an engaging and accessible tone, Religion in America probes the dynamics of religious beliefs and behaviors of Americans in recent decades. Charting trends over time using demographic data, the book examines how patterns of religious affiliation, service attendance, and prayer vary by race and ethnicity, social class, and gender. The authors identify demographic processes such as birth, death, and migration, as well as change in education, employment, and families, as central to why some individuals and congregations experience religious change while others hold steady. By tracing the historical roots of the recently intensifying association between a person's religious affiliation and their political party, the authors reveal how population change is a key factor in the anxiety and upheaval experienced by Americans today. Religion in America challenges students to examine the demographic data alongside everyday accounts of how religion is experienced differently across social groups to better understand the role that religion plays in the lives of Americans today and how that is changing"--